Antecedents of bullying victimisation in adolescents: a fresh look at Aotearoa New Zealand - Birchall M; Drummond A; Williams M (Taylor & Francis Group, 2024)
Research has consistently demonstrated that the prevalence of school bullying in Aotearoa New Zealand exceeds those observed in other developed countries. Despite the need to understand the risk and protective factors for bullying victimisation, there remains a paucity of research in the New Zealand context. The present study aimed to investigate the risk factors for bullying victimisation by conducting a secondary data analysis on a large and representative sample of 15-year-olds from New Zealand using data collected during the 2018 Programme for International Student Assessment (N = 4137). A multiple regression analysis identified eight risk factors which were significantly associated with at least one form of school bullying. The strongest effects indicated that increased parental support and school belonging were associated with lower victimisation, while classroom disorder and school competitiveness were associated with greater victimisation risk. The implications of these findings for future research are discussed.
Keywords: Peer victimisation; Risk factors; PISA; direct bullying; indirect bullying